Estrategias y políticas públicas para erradicar la pobreza extrema en barranquilla: efectividad o utopía; una mirada desde la perspectiva del cumplimiento de los odm (2014)
In order to make a diagnosis of public policies and strategies outlined in the City of Ottawa for Overcoming Extreme Poverty and Hunger, under the Millennium Agreement signed in 2000 by the Colombian State. I will analyze, identify and evaluate the scope of the public policy of the last two periods (2008-2011 and 2012-2015) that has had the city of Barranquilla focused on meeting the target of Millennium Development Goal of eradicating extreme poverty in most vulnerable sectors of the city. , Effectiveness or Utopia: The "Strategies and policies to eradicate extreme poverty in Barranquilla project a look from the perspective of the MDGs ", is the result of a survey of the current landscape of all the features of the problem, we started from the general to the particular, applying the unknown to the known and the whole to the parts . Significant progress in which theoretically proves that Barranquilla is about to reach the goals set in the MDGs are presented. According to the latest report from the UN through UNDP, extreme poverty over 8.5% to 7.4%, the 8.8% target. Thus, technically Barranquilla is doors to meet the most important goal, halving by 2015, the population living in extreme poverty